(untitled) (Journal of Informatics Education and Research, 2025)
This study examines the organization of self-generated resources for charitable organizations in both Algeria and Saudi Arabia, employing a comparative approach to highlight the similarities and differences between the two systems. It reveals that Algerian legislation, particularly Law 12/06 concerning associations, limits self-generated resources to public subsidies, membership fees, and revenues from the association’s activities and assets, subjecting them to rigorous financial oversight without clearly defined criteria for granting subsidies. In contrast, the Saudi system for associations and non-profit organizations has broadened sources of self-financing by adding tax and customs exemptions, the possibility of investing financial surpluses, and managing projects for governmental or private entities, thereby enhancing the financial sustainability of these organizations. The study concludes that Saudi legislation is more flexible in diversifying resources compared to Algerian legislation.